2016
DOI: 10.14748/sssp.v1i2.1355
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient safety climate in accident and emergency departments in Cyprus

Abstract: INTRODUCTION:The aim of the study is to evaluate safety climate in the accident and emergency (A&E) departments in Cyprus. This would help for an assessment of the general patient safety environment and could be used as a starting point for the establishment of a quality management system, which ensures patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Theoretical Framework As underlined above, patient safety is a crucial component of healthcare quality [2,9]. Poor communication among professionals, improper leadership or teamwork, insufficient staff knowledge of safety processes, an unsupportive safety culture in healthcare, and a lack of reporting systems and analysis of adverse events are a few of the common flaws in patient-safety structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical Framework As underlined above, patient safety is a crucial component of healthcare quality [2,9]. Poor communication among professionals, improper leadership or teamwork, insufficient staff knowledge of safety processes, an unsupportive safety culture in healthcare, and a lack of reporting systems and analysis of adverse events are a few of the common flaws in patient-safety structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the results of Nicolaides and Dimova's study, which evaluated PSC based on 6 dimensions, showed that the maximum and minimum scores were related to job satisfaction and stress detection, respectively. Also, a robust inverse correlation was found between labor intensity and employees' overall impressions of safety climate (-0.72) (27). The results of Chakravarty's investigation on the hospitals in India showed no difference between patient safety index scores.…”
Section: Discussionmentioning
confidence: 95%